FAKTOR YANG MEMENGARUHI AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Soesanto, Friska Rama; Viriany, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The objective of this study is to determine the effect of profitability, leverage, and liquidity towards tax aggresiveness. This research uses secondary data from manufacturing companies that is listed on the Indonesian Stock Exchange during the period of 2018-2020. The sample is selected using purposive sampling and amounted to 79 companies. The data is processed by using Eviews 12. Outputs obtained from this study indicates that leverage has a positive and significant influence towards tax aggressiveness. Profitability and liquidity has a negative and not significant influence on tax aggresiveness.